Can cognitive function tests discriminate between patients with glioma and healthy controls prior to treatment? A systematic review - Laura Standen; Aiman Aslam; Roisin Curran; Christina Derksen; Dharani Yerrakalva; Daisy McInnerney; Paul M. Brennan; Fiona M. Walter; Suzanne E. Scott (PLoS ONE, 2025)
Background Brain tumours affect 7 per 100,000 people in the UK, glioma being most prevalent, with only 12% five-year survival rates and devastating impacts. Primary care triage tools could facilitate earlier detection of glioma. One option for triage is cognitive function testing. The aim of this systematic review was to determine if cognitive function tests can discriminate between patients with glioma and healthy controls, and their potential suitability for primary care use. Methods Studies were included that conducted cognitive function tests with adult patients with glioma, prior to treatment, compared to healthy controls. Two independent researchers performed screening and data extraction. The primary outcome explored test discrimination between people with glioma and healthy controls. Results Seventeen studies were identified. Findings indicated multiple cognitive function and language function have potential discriminatory capacity between patients with glioma and healthy controls. Over half of cognitive function tests measuring multiple cognitive functions (59%, n = 17) and language function (54%, n = 30) found significant differences between patients with glioma and healthy controls with medium or large effect size. The Montreal Cognitive Assessment has short test duration, high feasibility and acceptability, suggesting potential primary care suitability. Further acceptability and feasibility studies are needed for other potential tests. Conclusions Acknowledging high heterogeneity of included studies, this review suggests tests of multiple cognitive functions or language could support primary care practitioners with decision-making for urgent neuroimaging referral. However, interpretations should be treated with caution and the applicability to primary care requires further exploration. Prospero registration number: CRD42023408671